Penerapan Algoritma C 5.0 Dalam Analisa Data Potensi Pertanian dan Perternakan (Studi Kasus: Unit Pembinaan Perlindungan Tanaman (UPPT) Biru-Biru) - Nurnia Zamasi; Nelly Astuti Hasibuan; Suginam Suginam (Journal of Informatics Management and Information Technology, 2021)
The problems faced at UPPT in each area in the form of productive land being converted into residential, industrial, and business centers can result in insufficient land area for farming and livestock and bad weather conditions. One way to analyze this data is to apply or use data mining techniques. Where data mining is the process of analyzing large data into information to determine patterns from the conclusions of the analyzed data. The application of the C 50 method which will later dig up existing data and will form a decision tree.By analyzing data on agricultural and livestock potential, the UPPT holds outreach in areas where the type of business is farming and livestock so that it does not have an impact on community income and also reduces losses in trying to farm and raise livestock.